Children's Gross Motor Development: Analysis of the influence of Sensory Path Media with Clapping Games - Siregar, Annisa; Heldanita, Heldanita; Suryanti, Dewi Sri; Susanti, Fatimah Depi; Irawan, Yossy; Samaun, Salina bt; Rohayani, Farida (Jurnal PG-PAUD, 2024)
This research aims to determine the effect of sensory path media using clapping games on the gross motor development of children aged 5-6 years at Raudhatul Athfal Al Fattah Pir Trans Sosa. This research uses a quantitative experimental method using a one group pretest posttest research design with a t-test using the formula tcount>ttable. If tcount>ttable Ho is rejected and Ha is accepted. Data analysis used SPSS Ver 25. Research subjects were teachers and early childhood children in group B aged 5-6 years at Raudhatul Athfal Al Fattah. Data collection techniques are observation, tests and documentation. The results of the research showed that there was an increase in gross motor development in the Kindergarten B group at Raudhatul Athfal Al Fattah Pir Trans Sosa by 84.2% in the high category with a normalized gain formula. The statistical t test results have a sig value of 0.000 < 0.05 with tcount 21.258 > ttable 1.753050. So Ho was rejected and Ha was accepted so that the sensory path media with clapping games had an effect on the gross motor development of children aged 5-6 years at Raudhatul Athfal Al Fattah Pir Trans Sosa. This research emphasizes the importance of media to support children's gross motor development through direct experience, namely using sensory path media with clapping games. This research can help teachers to obtain an overview of media that can be used to improve children's gross motor development. Schools/educational institutions can also use sensory path media as a means of developing children's gross motor skills. This research uses sensory path media combined with clapping games to improve children's gross motor development. Attractive sensory path media with creative colors and clapping games with body coordination to improve children's gross motor development. Keywords: Gross Motor, Sensory Path, Early Childhood